1990
DOI: 10.1029/rs025i004p00595
|View full text |Cite
|
Sign up to set email alerts
|

Mesospheric wind and aspect sensitivity measurements at Jicamarca using radar interferometry and poststatistics steering techniques

Abstract: Spectral and cross‐spectral signatures of lower mesospheric radar returns are investigated and modeled. Aspect sensitivity of radar echoes and the horizontal, vertical, and random components of atmospheric fluid velocity are estimated. Estimated random velocity magnitudes of ∼0.2 m/s during a specific lower mesospheric scattering event are smaller than corresponding Doppler spectral widths of ∼1 m/s. During the same event, aspect sensitivity variations as large as ∼10 dB/deg were observed. Higher mesospheric r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

1990
1990
2019
2019

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(8 citation statements)
references
References 13 publications
1
7
0
Order By: Relevance
“…The phase calibration techniques are mainly based on the artificial or natural scatterers at known location, for example, the aircraft (e.g., Chen et al, 2002) and the injection of test signals into various system components (e.g., . On the other hand, some assumptions are employed to calibrate the radar system phase offsets, for example, that the mean scattering position of lower and higher mesospheric returns over a suitably long observation period is centered on the zenith (e.g., Kudeki et al, 1990) and that the number of meteor occurrences with varying height range satisfies the Gauss distribution (e.g., Holdsworth, Tsutsumi, et al, 2004). Solomon et al (1998) reported the use of meteor echoes for phase calibration of an over-the-horizon radar.…”
Section: Technical Reports: Methodsmentioning
confidence: 99%
“…The phase calibration techniques are mainly based on the artificial or natural scatterers at known location, for example, the aircraft (e.g., Chen et al, 2002) and the injection of test signals into various system components (e.g., . On the other hand, some assumptions are employed to calibrate the radar system phase offsets, for example, that the mean scattering position of lower and higher mesospheric returns over a suitably long observation period is centered on the zenith (e.g., Kudeki et al, 1990) and that the number of meteor occurrences with varying height range satisfies the Gauss distribution (e.g., Holdsworth, Tsutsumi, et al, 2004). Solomon et al (1998) reported the use of meteor echoes for phase calibration of an over-the-horizon radar.…”
Section: Technical Reports: Methodsmentioning
confidence: 99%
“…Clearly, the results discussed above are very tentative and preliminary and need to be further investigated. One possible approach is the simultaneous use of the FDI and radar interferometry (RI) [e.g., Kudeki, 1988;Kudeki et al, 1990] techniques to achieve comparable range and angular resolutions. If the lower mesospheric layers are indeed blobby in the horizontal direction, RI data might be able to isolate the corresponding angular positions.…”
Section: Admittedly the Time Series Exhibited Inmentioning
confidence: 99%
“…An important point underlined in Sheth et al (), that is crucial to what we are describing here, is that for MST radars the shape of the backscattered signal spectrum is largely determined by the antenna beam shape of the radar as a consequence of a “beam broadening” mechanism (as opposed to the thermodynamics of the scattering plasma which is the dominant factor for ISR tehnique). When the beam broadening mechanism (e.g., Kudeki et al, ) dominates, the MST signal spectrum becomes a rescaled version of the antenna “two‐way” angular beam function (the product of the radar antenna transmission gain and receiving area functions in 2‐D) collapsed to 1‐D in the direction of the prevailing mesospheric wind advecting the electron density irregularities that cause the backscattering of the transmitted radar pulse. The modeling details of this mapping (including “aspect sensitivity” caused modifications that may be important) can be found in MST radar literature—see Kudeki et al () for a comprehensive description—but it is sufficient for our descriptions in this paper to understand that MST radar returns would be expected to display single peaked Doppler spectra if the two‐way radar beam were free of sidelobes, and, conversely, display multipeaked shapes if/when beam sidelobes were nonnegligible.…”
Section: Introductionmentioning
confidence: 99%